2021
DOI: 10.3389/ffunb.2021.756990
|View full text |Cite
|
Sign up to set email alerts
|

Ypd1 Is an Essential Protein of the Major Fungal Pathogen Aspergillus fumigatus and a Key Element in the Phosphorelay That Is Targeted by the Antifungal Drug Fludioxonil

Abstract: Aspergillus fumigatus is a major fungal pathogen causing life threatening infections in immunocompromised humans and certain animals. The HOG pathway is for two reasons interesting in this context: firstly, it is a stress signaling pathway that contributes to the ability of this pathogen to adapt to various stress conditions and secondly, it is the target of antifungal agents, such as fludioxonil or pyrrolnitrin. In this study, we demonstrate that Ypd1 is an essential protein in A. fumigatus. As the central co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In A. fumigatus , Ypd1 is present in the whole nucleo-cytoplasm and shuttles between both compartments. Ypd1 translocates much faster than TcsC ( 12 ), which is likely due to its much smaller size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In A. fumigatus , Ypd1 is present in the whole nucleo-cytoplasm and shuttles between both compartments. Ypd1 translocates much faster than TcsC ( 12 ), which is likely due to its much smaller size.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data showed that TcsC executes its activity via the histidine phosphotransfer (Hpt) protein Ypd1 and the downstream response regulators Skn7 and SskA ( 11 , 12 ); all four proteins form a so-called multistep phosphorelay ( 13 ). Our current knowledge of the mechanisms that activate TcsC and other group III HHK is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Ypd1 protein was selected for the in silico study. The Ypd1 protein is important for the physiology of selected fungi as it contributes to the ability of the pathogen to adapt to various stressed conditions (Schruefer, 2021). The phytochemicals (ligands) from the Punica granatum were selected to analyze their inhibition ability to the functioning of the selected protein.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its key role in the HOG signaling pathway, MoYPD1 appears to positively and negatively influence genes involved in other stress adaptation processes and virulence 6 . Studies on Ypd1p homologs in other fungi, such as Candida albicans and Aspergillus fumigatus , have shown that green fluorescent protein (GFP)-fused Ypd1p shuttles between the cytoplasm and the nucleus 28 , 29 . Therefore, it is conceivable that MoYpd1p interacts with targets in both the cytosol and nucleus.…”
Section: Introductionmentioning
confidence: 99%